Cubic boron nitride based composite material and method for producing same

JP7634013B2Active Publication Date: 2025-02-20DIAMOND INNOVATIONS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022538410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-12-10
Publication Date
2025-02-20
Estimated Expiration
2040-12-10

Smart Images

  • Figure 0007634013000005
    Figure 0007634013000005
  • Figure 0007634013000006
    Figure 0007634013000006
  • Figure 0007634013000007
    Figure 0007634013000007
Patent Text Reader

Abstract

The binder is composed of about 30-65% by volume of cBN, about 15-45% by volume of titanium (Ti), about 2-20% by volume of zirconium dioxide (ZrO2), and about 3-15% by volume of cobalt-tungsten-boride (Co x W y B z ), and a cubic boron nitride (cBN)-based composite containing approximately 2-15 volume percent aluminum oxide (Al2O3).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE This disclosure relates generally to composite materials formed from cubic boron nitride and methods of making and using same. In particular, this disclosure relates to composite materials useful in machining difficult-to-cut materials. [Background technology]

[0002] In the following background description, reference is made to certain structures and / or methods. However, the following references should not be construed as an admission that these structures and / or methods constitute prior art. Applicants expressly reserve the right to demonstrate that such structures and / or methods are not admitted as prior art.

[0003] Cubic boron nitride (cBN) is an ultra-hard material that is often used to form cBN-based composites for cutting and / or machining applications. To improve resistance to chemical wear, certain ceramic materials, such as alumina (Al2O3), titanium nitride (TiN), and silicon nitride (Si3N4), can be blended with cBN. However, such ceramic materials may not have sufficient hardness and / or heat resistance to perform optimally when machining hard materials. For example, existing cBN-based composites may still exhibit rapid wear, fracture, and / or breakage when cutting or machining difficult-to-cut materials, especially heat-resistant superalloys. Thus, there is a need for better cBN-based composites with improved cutting and machining properties for difficult-to-cut materials. Summary of the Invention

[0004] The binder is made of about 30-65% by volume of cBN, about 15-45% by volume of titanium (Ti), about 2-20% by volume of zirconium dioxide (ZrO2), about 3-15% by volume of cobalt-tungsten-boride (Co x W y B z ), and about 2-15 volume percent aluminum oxide (Al2O3) are provided.

[0005] Also provided is a cutting tool or cutter that can be used to cut superalloys including, for example, Inconel 718, Inconel 625, Alloy 188, Haynes 25, Alloy L605, and / or A 286. The cutting tool may include a sintered cubic boron nitride (cBN) based compact. The cBN based composite may include about 30-65% by volume cBN, about 15-45% by volume titanium (Ti)-containing binder, about 2-20% by volume zirconium dioxide (ZrO2), about 3-15% by volume cobalt-tungsten-boride (CoBN), about 15-45% by volume titanium (Ti)-containing binder, ... x W y B z ), and about 2-15 volume % aluminum oxide (Al2O3).

[0006] Additionally, a method of forming a cubic boron nitride (cBN) based composite is provided. The method includes mixing powders of a cBN based formulation to form a cBN based composite to form a first mixture. The cBN based composite may include about 30-65% by volume cBN, about 15-45% by volume titanium (Ti)-containing binder, about 2-20% by volume zirconium dioxide (ZrO2), about 3-15% by volume cobalt-tungsten-boride (CoBN), about 15-20% by volume tungsten-boride (TBO ... x W y B z ), and about 2-15 volume percent aluminum oxide (Al2O3). The method includes drying the first mixture to form a second mixture and filling one or more refractory molds with the second mixture. The method also includes sintering the second mixture at high pressure and high temperature conditions.

[0007] Also provided is a method for making a cutting tool including a sintered cubic boron nitride (cBN)-based composite. The method includes blending powders of a cBN-based formulation to form a cBN-based composite to form a first mixture. The cBN-based composite may include about 30-65% by volume cBN, about 15-45% by volume titanium (Ti)-containing binder, about 2-20% by volume zirconium dioxide (ZrO2), about 3-15% by volume cobalt-tungsten-boride (CoBN), about 15-20% by volume titanium-containing binder, ... x W y B z ), and about 2-15 volume percent aluminum oxide (Al2O3). The method includes drying the first mixture to form a second mixture and filling one or more refractory molds with the second mixture. The method also includes sintering the second mixture under high pressure and high temperature conditions. Further, the method includes forming the sintered body into a shape suitable for cutting materials. Optionally, the method includes attaching the sintered body to a tool body.

[0008] The foregoing summary, as well as the following detailed description of the embodiments, can be better understood when read in conjunction with the appended drawings, in which: It is understood that the depicted embodiments are not limited to the precise arrangements and instrumentalities shown. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 illustrates an exemplary process for forming a cBN-based sintered body or composite. [Diagram 2] FIG. 1 shows XRD spectra illustrating the phases present in an exemplary cBN-based sintered body or composite. [Diagram 3] FIG. 2 shows an XRD spectrum illustrating the phases present in another exemplary cBN-based sintered body or composite. [Figure 4] FIG. 2 shows an XRD spectrum illustrating the phases present in another exemplary cBN-based sintered body or composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure relates to composites or sintered bodies formed from cubic boron nitride (cBN) and methods of making and using the same. In particular, the present disclosure relates to improved cBN-based composites useful for cutting and machining difficult-to-cut materials, such as superalloys for applications requiring high strength at high temperatures. For example, the cBN-based composites (e.g., sintered bodies) disclosed herein can be used to cut and / or machine nickel-based superalloys (e.g., Inconel 718, Inconel 625), cobalt-based superalloys (e.g., Alloy 188, Haynes 25, Alloy L605), iron-based superalloys (e.g., A286), or any material having mechanical properties similar to, inferior to, or superior to these superalloys.

[0011] The cBN-based composite materials disclosed herein can include, among other improvements, greater wear resistance, toughness, chemical resistance, hardness, and / or high temperature hardness. These improvements can be achieved by using cBN in the proportions disclosed herein, titanium-containing binders ("Ti-containing binders") such as Ti-based nitrides, carbides, and / or carbonitrides, zirconia (ZrO2), cobalt-tungsten-borides (CoWB, CoW2B2, W3CoB3, or combinations thereof). x W y B z The strength of the cBN-based formulation is at least partially due to a combination of cBN, alumina (Al2O3), and / or titanium diboride (TiB2). The present disclosure also describes a method for forming the cBN-based formulation into a sintered body that can be used for cutting or machining difficult-to-cut materials.

[0012] With the above in mind, Tables 1 and 2 list exemplary compositions of cBN-based composites (e.g., sintered bodies). An exemplary process for forming a cBN-based composite is shown in the flow diagram of Figure 1. In Tables 1 and 2, all volume percents (vol%) listed are based on the total volume% of the cBN-based composite. TIFF0007634013000001.tif45170TIFF0007634013000002.tif46170

[0013] The cBN-based composite (e.g., sintered body) may include about 30-65 volume % cBN, about 40-60 volume % cBN, or about 45-55 volume % cBN. Additionally, the cBN-based composite may include about 15-45 volume %, about 20-40 volume %, or about 15-30 volume % Ti-containing binder. Additionally, the cBN-based composite may include about 2-20 volume % ZrO2, about 5-13 volume % ZrO2, or about 7-10 volume % ZrO2. As provided, the cBN-based composite may include about 3-15 volume % Co. x W y B z , about 4 to 13 volume percent Co x W y B z , about 5-10% by volume of Co x W y B z The cBN-based composite material may further include about 2-15 vol% Al2O3, about 2-15 vol% Al2O3, about 4-13 vol% Al2O3, or about 5-10 vol% Al2O3. Additionally, the cBN-based composite material may include about 10 vol% or less TiB2 (e.g., about 0.01 vol% to about 10 vol% TiB2, about 0.01 vol% to about 8 vol% TiB2, about 0.01 vol% to about 5 vol% TiB2, or about 2 vol% to about 10 vol% TiB2, or about 5 vol% to about 10 vol% TiB2). The Ti-containing binders disclosed herein can include any suitable Ti-based nitride, oxide, and / or carbide, such as titanium nitride (TiN), titanium carbonitride (TiCN), titanium carbide (TiC), titanium carbonitride (TiCON), titanium oxynitride (TiNO), or combinations thereof.

[0014] FIG. 1 illustrates an exemplary process 100 for forming a cBN-based composite material (e.g., a sintered body). The exemplary process 100 includes mixing powders of a cBN-based formulation to form a first mixture (step 102). The cBN-based formulation may include or consist of one or more powder formulations including, for example, a powder including or consisting of cBN, a powder including or consisting of a Ti-based material such as Ti and / or a Ti-containing binder, a powder including or consisting of zirconium, for example, a powder including ZrO2, a powder including or consisting of aluminum, a powder including or consisting of W, a powder including or consisting of Co, a powder including or consisting of B, and combinations thereof. Step 102 includes providing a powder that can be used to form a cBN-based composite material disclosed herein (e.g., the compositions shown in Tables 1 and 2). The powders are nano-sized and / or micron-sized powders, for example, the average particle size of the powders of the cBN-based formulation can be in the nanometer (nm) or micrometer (μm) range, i.e., about 100 nm to 10 μm. Step 102 can include mixing the powders to form a mixture or slurry. The powders can be mixed using any suitable grinding or blending technique (e.g., attrition mill, ball mill, etc.). The powders can be ground or blended with any suitable solvent, such as ethanol, isopropanol, acetone, methanol, hexane, heptane, or combinations thereof, to form a first mixture. The grinding conditions (e.g., time, revolutions per minute, type of media or solvent, etc.) can be adjusted or tuned according to the size and / or type of mill used to achieve the desired mixing effect (e.g., powder distribution and uniformity).

[0015] The process 100 may include drying the first mixture to form a second mixture, step 104. The first mixture or slurry formed in step 102 may be dried using any suitable technique, such as vacuum drying, air drying, etc., to substantially remove the solvent and / or binder in the first mixture.

[0016] The process 100 may include filling a refractory mold with the second mixture (step 106). The refractory mold may be made of any suitable material, including any suitable refractory metal, such as tantalum, niobium, molybdenum, and the like. Step 106 may include disposing the second mixture on a cemented carbide (WC-Co) substrate disposed in the refractory mold. Additionally, step 106 may also include filling the refractory mold with the second mixture and capping with a WC-Co disk that fits snugly within the mold opening. Step 106 may also include sealing the refractory mold containing the second mixture and / or the WC-Co substrate / disc.

[0017] The process 100 may include sintering the second mixture at high pressure, high temperature conditions (step 108). The closed refractory mold containing the second mixture may be placed in a high pressure, high temperature (HPHT) cell and HPHT sintering conditions are applied to form a cBN-based composite material (e.g., a sintered body) disclosed herein. Step 108 may include sintering the second mixture at a pressure of about 5 gigapascals (GPa) to 8 GPa and a temperature of about 1300 to 1600°C. Step 108 may include sintering the second mixture at a pressure of at least 4 GPa and a temperature of at least 1100°C. The cBN-based composite material (e.g., sintered body) can have a grain size in the nanometer or submicron range, for example, about 0.1-10 μm, about 0.1-8 μm, about 0.1-6 μm, about 0.1-4 μm, about 0.1-2 μm, about 2-4 μm, about 0.5-1.5 μm, or about 0.1-1 μm.

[0018] The cBN-based composites (e.g., sintered bodies) formed according to process 100 can be used to machine difficult-to-cut materials. For example, the cBN-based composites formed according to process 100 can be formed into cutting tools for machining high strength superalloys, including nickel-based superalloys (e.g., Inconel 718, Inconel 625), cobalt-based superalloys (e.g., Alloy 188, Haynes 25, Alloy L605), iron-based superalloys (e.g., A 286), or any materials having mechanical properties similar to, inferior to, or superior to these superalloys.

[0019] Without wishing to be bound by any particular theory, it is believed that the compositions and phases of the cBN-based composites (e.g., sintered bodies) disclosed herein may contribute to improved wear resistance, toughness, chemical resistance, hardness, hot hardness, or a combination thereof, thereby improving cuttability and machinability. Table 3 shows exemplary cutting performance using cutting tools made with the cBN-based composites (e.g., sintered bodies) disclosed herein. TIFF0007634013000003.tif118170

[0020] In the illustrative example, Samples 1-10 represent cutting tools made with cBN-based composites (e.g., sintered bodies) formed according to the compositions shown in Tables 1 and 2 and process 100 described in FIG. 1. Cutting tests were performed on Inconel 718 at a speed of 350 meters per minute (m / min) and a feed rate of 0.15 millimeters per revolution (mm / rev) with coolant continuously applied to the cutting interface. Cutting tests were performed to a predetermined flank wear of 0.25 mm for Samples 1-10. The rightmost column of Table 3 lists the cut distance in kilometers (km) at the end of tool life. If there was chipping of the sample during the cutting test, the test was pre-terminated before the predetermined flank wear was reached and is indicated by an asterisk. 「*」indicates the cutting distance when chipping of the sample occurred. For example, in sample 5, chipping occurred in two of the three cutting tests at a cutting distance of 0.1 km, and in sample 6, chipping occurred in one of the two cutting tests at a cutting distance of 0.8 km.

[0021] Both Sample 1 and Sample 2 have a cBN grain size of about 2 to 4 μm, and each contains about 65 volume % cBN. x W y B z It does not contain ZrO2 or ZrO3. The difference between sample 1 and sample 2 is that sample 1 contains TiCN binder, while sample 2 contains TiN binder. The cutting distances are 0.6km and 0.6km for sample 1, and 0.6km and 0.7km for sample 2. There is no significant difference between the cutting distances of sample 1 and sample 2.

[0022] Both Sample 3 and Sample 4 have a cBN grain size of about 2 to 4 μm, and each contains about 50 volume % cBN. x W y B z It does not contain ZrO2 or ZrO3. The difference between sample 3 and sample 4 is that sample 4 contains TiCN binder, while sample 3 contains TiN binder. The cutting distances are 0.7km and 0.8km for sample 3, and 0.7km and 0.7km for sample 4. There is no significant difference between the cutting distances of sample 3 and sample 4.

[0023] Both Sample 5 and Sample 6 have a cBN grain size of about 0 to 1 μm, and both contain ZrO2 (e.g., about 3 to 15 vol.%) and about 50 vol.% cBN, and both contain Co. x W y B z The difference between sample 5 and sample 6 is that sample 5 contains TiCN binder, while sample 6 contains TiN binder. The cutting distances are 1.2 km, 0.1 km (sample chipping occurred), and 0.1 km (sample chipping occurred) for sample 5, and 1.1 km and 0.8 km (sample chipping occurred) for sample 6. There is no significant difference between the cutting distances of sample 5 and sample 6.

[0024] Without wishing to be bound by any particular theory, it is believed that Ti-containing binders (e.g., TiN, TiCN, TiC, TiCON, TiNO) can function as binders and generally have similar effects on improving cutting ability. For example, based on a comparison of the cutting distances of Samples 1 and 2, Samples 3 and 4, and Samples 5 and 6, TiCN and TiN appear to be interchangeable in terms of their contribution to improving cutting ability.

[0025] Both Sample 6 and Sample 7 have a cBN grain size of about 0 to 1 μm, and each contains 50 volume % cBN, TiN, and ZrO2. The difference between Sample 6 and Sample 7 is that Sample 7 contains Co x W y B z The cutting distances were 1.1 km and 0.8 km for sample 6 (where chipping occurred), and 1.4 km and 1.4 km for sample 7. Without wishing to be bound by any particular theory, it is believed that the x W y B z It is believed that the presence of may contribute to improved cutting ability.

[0026] Both Sample 7 and Sample 8 have a cBN grain size of about 0 to 1 μm, and both contain 50% by volume of cBN, TiN, and Co. x W y B z The difference between Sample 7 and Sample 8 is that Sample 7 contains ZrO2 and Sample 8 does not. The cutting distances are 1.4 km and 1.4 km for Sample 7 and 1.0 km for Sample 8. Without wishing to be bound by any particular theory, it is believed that the presence of ZrO2 may contribute to improved cutting ability.

[0027] Sample 9 has a cBN grain size of about 0.5 to 1.5 μm and contains 50 volume % cBN, TiN, and TiCN, but does not contain Co. x W y B zand no ZrO2. The difference between sample 9 and samples 3 and 4 is that sample 9 has a slightly smaller cBN grain size and contains both TiN and TiCN. The cutting distances for sample 9 are 0.7 km and 0.7 km, which are similar to samples 3 and 4. Based on the comparison, the presence of TiN only, TiCN only, and both TiN and TiCN appear to contribute similarly to cutting ability, and TiN and TiCN appear to be substitutable.

[0028] Samples 7 and 10 both have a cBN grain size of about 0-1 μm, and both contain 50 vol.% cBN, 3-8 vol.% Co. x W y B z , and 3-15 volume % ZrO2. The difference between sample 7 and sample 10 is that sample 7 contains TiN, while sample 10 contains TiCN. The cutting distances are 1.4 km and 1.4 km for sample 7, and 1.3 km and 1.3 km for sample 10. There is no significant difference between the cutting distances of sample 7 and sample 10.

[0029] Without wishing to be bound by any particular theory, it is believed that the specific combination and / or elimination of certain crystalline phases may contribute to the improved cutting ability of the cBN-based composite materials (e.g., sintered bodies) disclosed herein. For example, Co x W y B z ZrO2, for example, exists in cBN-based composites (e.g., sintered bodies) as the crystalline phases crystalline CoWB, crystalline CoW2B2, and crystalline W3CoB3, thereby contributing to improved cutting ability. ZrO2, for example, exists in cBN-based composites (e.g., sintered bodies) as cubic ZrO2 (c-ZrO2) and / or monoclinic ZrO2 (m-ZrO2), thereby contributing to improved cutting ability.

[0030] In some embodiments, the W / Co weight ratio of the cBN-based composite (e.g., sintered body) can be from about 3 to about 8. x W y B zThe composite may include a mixture of crystalline CoWB (e.g., W / Co=6.2) and / or crystalline CoW2B2 (e.g., W / Co=3.1), and the W / Co weight ratio of the composite may range from about 3 to about 8, or from about 3 to about 7. In some embodiments, the Co present in the cBN-based composite (e.g., sintered body) may be in the range of about 3 to about 8, or about 3 to about 7. x W y B z is W2Co 21 B6 can be excluded.

[0031] In some embodiments, the cBN-based composites (e.g., sintered bodies) disclosed herein can be substantially free of or exclude aluminum diboride (AlB2). In some embodiments, the cBN-based composites (e.g., sintered bodies) disclosed herein can include very low or very small amounts of TiB2, e.g., less than 1% by volume TiB2. In some embodiments, the cBN-based composites (e.g., sintered bodies) can be substantially free of or exclude TiB2.

[0032] X-ray diffraction (XRD) can be performed on the cBN-based composite materials (e.g., sintered bodies) disclosed herein to identify the phases present. Figures 2, 3, and 4 show XRD spectra from Sample 6, Sample 7, and Sample 10, respectively. The XRD spectra in Figures 2 and 3 demonstrate that both Sample 6 and Sample 7 contain cBN, TiN, and ZrO2 phases. The ZrO2 phase is present as c-ZrO2 in Sample 6 and as c-ZrO2 and m-ZrO2 in Sample 7. The XRD spectra in Figures 2 and 3 also demonstrate that Sample 7 contains Co x W y B z Sample 6 contains Co x W y B z It has been demonstrated that the product does not contain Co. x W y B z The presence of Co is believed to contribute to improving cutting ability. x W y B zis present in sample 7 as crystalline CoWB and crystalline CoW2B2. The XRD spectra in Figures 3 and 4 show that both sample 7 and sample 10 are composed of cBN, Co x W y B z , Al2O3, and ZrO2 phases, and sample 7 contains a TiN phase, whereas sample 10 contains a TiCN phase.

[0033] Table 4 shows the XRD peak information of Sample 6, Sample 7, and Sample 10. Table 4 lists the peak positions (2-theta degrees) and normalized peak intensities of various phases present in Sample 6, Sample 7, and Sample 10. Table 4 also lists the peak intensity ratio between CoW2B2 and Ti-containing binder. In the described embodiment, the peak intensity ratio is determined based on the I2 peak intensity of CoW2B2 phase and the It2 peak intensity of TiCN or TiN phase. The peak ratio of CoW2B2 to Ti-containing binder is 0% for Sample 6, 32.8% (31.37 / 95.54=32.8%) for Sample 7, and 33.7% (28.3 / 83.9=33.7%) for Sample 10. In some embodiments, the peak ratio of CoW2B2 to Ti-containing binder in the cBN-based composite is 10%, 10%-40%, 20%-40%, 25%-40%, 30%-35%, 31%-34%, about 33%, or greater than about 32%, which may help improve the cutting ability of the cBN-based composite.

[0034] As seen throughout the XRD spectrum, the CoxWyBz phase has at least one peak with an intensity at least 10% of the peak intensity of the highest Ti-based ceramic. TIFF0007634013000004.tif90170

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the protected subject matter described herein belongs.

[0036] When a range of values, such as a concentration range, percentage range, or ratio range, is provided, it is understood that each intervening value, to the tenth of the unit of the lower limit between the upper and lower limits of that range, and any other stated or intervening value in that stated range, is encompassed within the described coverage, unless the context clearly dictates otherwise. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges, and such embodiments are also encompassed within the described coverage, subject to any specifically excluded limits of the stated range. Where a stated range includes one or both of the limits, ranges excluding one or both of those included limits are also included in the described coverage.

[0037] The terms "a" and "an," as used above and elsewhere in this specification, should be understood to refer to "one or more" of the listed components. It will be clear to one of ordinary skill in the art that the use of the singular includes the plural, unless otherwise specified. Thus, the terms "a," "an," and "at least one" are used interchangeably in this application.

[0038] Unless otherwise indicated, all numbers expressing properties such as amounts, sizes, weights, reaction conditions, and the like of ingredients used in the specification and claims should be understood to be modified in all instances by the term "about". Throughout this application, the term "about" refers to ±10% of the numerical value of the number used, so that about 50% may mean a range of 45% to 55%. Thus, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximations that may vary depending on the desired properties sought to be obtained by the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0039] Throughout this application, descriptions of various embodiments use the term "comprising," however, it will be understood by those of ordinary skill in the art that in some instances an embodiment can be alternatively described using the terms "consisting essentially of" or "consisting of."

[0040] Although particular embodiments have been referenced, it will be apparent that other embodiments and variations can be devised by those skilled in the art without departing from the spirit and scope thereof, and it is intended that the appended claims be construed to include all such embodiments and equivalent variations.

Claims

1. 30 to 65 volume percent cBN; 15-45 vol. % titanium (Ti)-containing binder; 2 to 20% by volume of zirconium dioxide (ZrO 2 ). 3 to 15% by volume of cobalt-tungsten-boride (Co x W y B z ); and 2 to 15% by volume of aluminum oxide (Al 2 O 3 ) 1. A cubic boron nitride (cBN) based composite comprising:

2. Titanium diboride (TiB 2 2. The cBN-based composite of claim 1, further comprising:

3. A composite material comprising 45 to 55 volume percent cBN, 15 to 30 volume percent Ti-containing binder, 5 to 13 volume percent ZrO 2 , 5 to 10 volume percent Co x W y B z , 5 to 10% by volume of Al 2 O 3 2. The cBN-based composite of claim 1 , comprising:

4. Less than 10% by volume of TiB 2 4. The cBN-based composite of claim 3, further comprising:

5. Co x W y B z However, crystalline CoWB and crystalline CoW 2 B 2 , and crystalline W 3 CoB 3 10. The cBN-based composite of claim 1, comprising:

6. 2. The cBN-based composite of claim 1, wherein W and Co are present in a W / Co weight ratio of from 3 to 8.

7. 2. The cBN-based composite of claim 1, wherein the Ti-containing binder comprises titanium nitride (TiN), titanium carbonitride (TiCN), titanium carbide (TiC), titanium carbonitride (TiCON), titanium oxynitride (TiNO), or a combination thereof.

8. 10. The cBN-based composite of claim 1, wherein the cBN has a grain size of 0.1 micrometers (μm) to 4 μm.

9. 10. The cBN-based composite of claim 1, wherein the cBN has a grain size of 0.1 micrometers (μm) to 2 μm.

10. 10. The cBN-based composite of claim 1, wherein the cBN has a grain size of 0.1 micrometers (μm) to 1 μm.

11. 13. A cutting tool for cutting superalloys including Inconel 718, Inconel 625, Alloy 188, Haynes 25, Alloy L605, and / or A 286 comprising the cBN-based composite of claim 1.

12. mixing powders of a cubic boron nitride (cBN)-based compound for forming a cBN-based composite to form a first mixture; drying the first mixture to form a second mixture; filling one or more refractory molds with the second mixture; sintering the second mixture under high pressure and high temperature conditions; 1. A method of forming a cBN-based composite, comprising: cBN-based composites are 30 to 65 volume percent cBN; 15 to 45 volume percent of a titanium (Ti)-containing binder; 2 to 20% by volume of zirconium dioxide (ZrO 2 ), 3 to 15% by volume of cobalt-tungsten-boride (Co x W y B z ), and 2 to 15% by volume of aluminum oxide (Al 2 O 3 ) A method comprising:

13. 13. The method of claim 12, further comprising mixing the cBN-based formulation powder with one or more solvents comprising ethanol, isopropanol, acetone, methanol, hexane, heptane, or combinations thereof to form a first mixture.

14. The method of claim 12 , wherein drying the first mixture comprises vacuum drying the first mixture.

15. The method of claim 12, wherein filling the second mixture comprises placing the second mixture and a cemented carbide (WC-Co) substrate or disk into one or more refractory molds.

16. 13. The method of claim 12, further comprising sintering the second mixture at a pressure of at least 4 gigapascals (GPa) and a temperature of at least 1100°C.

17. The composition of claim 16, wherein the cBN is 30 to 65 volume percent; 15-45 vol. % titanium (Ti)-containing binder; 2 to 20% by volume of zirconium dioxide (ZrO 2 ). 3 to 15% by volume of cobalt-tungsten-boride (Co x W y B z ); and 2 to 15% by volume of aluminum oxide (Al 2 O 3 ) Sintered cubic boron nitride (cBN) based compacts comprising: Including cutting tools.

18. mixing powders of a cBN-based formulation for forming a sintered cBN-based compact to form a first mixture; drying the first mixture to form a second mixture; filling one or more refractory molds with the second mixture; sintering the second mixture under high pressure and high temperature conditions to form a sintered (cBN) based compact; 20. A method of forming the sintered (cBN) based compact of claim 17, comprising:

19. The sintered cBN-based compact is comprised of a sintered cBN-based compact having a volume of 45-55% by volume, a Ti-containing binder of 15-30% by volume, a ZrO of 5-13% by volume, and a sintered cBN-based compact having a volume of 45-55% by volume, and a Ti-containing binder of 15-30% by volume, a ZrO of 5-13 2 , 5 to 10 volume percent Co x W y B z , 5 to 10% by volume of Al 2 O 3 %, and less than 10 vol.% TiB 2 20. The cutting tool of claim 17, comprising:

20. Sintered cBN-based compacts include crystalline CoWB, crystalline CoW 2 B 2 , crystalline W 3 CoB 3 or a combination thereof and having a W / Co weight ratio of from 3 to 8.

Citation Information

Patent Citations

  • Sintered compact

    JP2002226273A

  • High content CBN-containing material, compact incorporating the same and method of making the same

    JP2007039329A

  • Composite molded articles formed from ceramics and low-volume cubic boronitrides, and production methods.

    JP2014520063A

  • Cubic boron nitride sintered body and method for making the same

    US20070134494A1

  • Cubic boron nitride sintered compact and coated cubic boron nitride sintered compact

    WO2010119962A1